THE ROLE OF INFORMATION TECHNOLOGIES IN DEVELOPING AUDITORY PERCEPTION AND PRONUNCIATION IN CHILDREN WITH COCHLEAR IMPLANTS - Sharipov Bayramali Sirojiddin ugli,Safarova Sanobar Omontoshevna (International Journal of Literature and Language Studies, 2026)
This article discusses the role of information technologies in developing auditory perception and pronunciation skills in children with cochlear implants. Cochlear implantation creates an opportunity for children with severe and profound hearing loss to perceive sound; however, hearing through an implant does not automatically lead to full speech understanding, correct pronunciation, or active verbal communication. Therefore, systematic, individualized, and scientifically grounded rehabilitation is required. The article analyzes the importance of digital tools, multimedia resources, interactive exercises, computer-based auditory training, mobile applications, online platforms, and electronic monitoring in the rehabilitation process. Special attention is given to designing individual lessons aimed at developing auditory attention, sound discrimination, phonemic hearing, speech comprehension, articulation, pronunciation automation, and communicative competence. The article emphasizes that information technologies should not replace the teacher, speech therapist, or surdopedagogue, but should serve as effective pedagogical tools that increase motivation, provide repeated practice, support visual-auditory integration, and help monitor progress. The proposed model can be used in rehabilitation centers, special education institutions, inclusive schools, and home-based intervention programs.